Taxonomic study of the Caliscelidae (Hemiptera: Fulgoromorpha: Fulgoroidea) from China - Chen, Xiang-Sheng; Gong, Nian (Zootaxa, 2025)
The Chinese planthopper family Caliscelidae (Hemiptera: Auchenorrhyncha: Fulgoroidea) is studied taxonomically. Two subfamilies, with five tribes, 21 genera and 53 species belonging to Caliscelidae are reported from China, including five new species and four genera and three species recorded from China for the first time. Five new species are discovered: Anthracidium maculatus sp. nov., Bambusicaliscelis nigritus sp. nov., Peltonotellus lobulus sp. nov., P. albulus sp. nov., and Caliscelis (Melanero) maculatum sp. nov. The genera Chirodisca Emeljanov, 1996, previously known from Indian subcontinent and Africa, Anthracidium Emeljanov, 2013, Annamatissus Gnezdilov & Bourgoin, 2014 and Cicimora Emeljanov, 1998, previously known from Vietnam as well as Chirodisca eximia (Stål, 1859), Annamatissus tami Gnezdilov & Soulier-Perkins, 2014 and Cicimora sicildia Emeljanov, 1998 are recorded from China for the first time. Keys to genera and species are given.